Living-related partial liver transplantation in unresectable liver metastatic colorectal cancer. A case report - O. H. Kotenko; I. O. Kotenko; M. S. Hryhorian; A. A. Minich; A. O. Matviienkiv; O. S. Mykhailiuk (Zaporožskij Medicinskij Žurnal)
Aim. The purpose of the article is to study the outcome of using living-related partial liver transplantation in the treatment of unresectable liver metastatic colorectal cancer.